An isolated phlebolith on the lip: an unusual case and review of the literature - Lima, Gabriela de Morais Gouvêa [UNESP]; Moraes, Renata Mendonça [UNESP]; Cavalcante, Ana Sueli Rodrigues [UNESP]; Carvalho, Yasmin Rodarte [UNESP]; Anbinder, Ana Lia [UNESP] (Hindawi Publishing Corporation, 2015)
Background. Calcified thrombi are a common finding, especially in the pelvic veins. There are generally multiple thrombi, and they are generally associated with vascular malformations. Design. Herein we report a rare case of a single labial phlebolith, not associated with any other vascular lesion. We aim to alert clinicians to the possibility of the occurrence of vascular thrombi in the mouth and to describe the clinical and histological characteristics of such lesions in order to simplify the diagnosis and treatment. Furthermore, we have reviewed the English-language literature published since 1970 reporting oral (including masticatory muscles) phleboliths. Results. Twenty-nine cases of phleboliths have been reported in the literature since 1970. Only three of the reported phleboliths were solitary and not associated with other vascular lesions, as in the case presented here. Conclusion. Although phleboliths not associated with other vascular lesions are not common, clinicians should be aware of the existence of this pathology and include it as differential diagnosis of oral lesions.